2003
DOI: 10.1161/01.cir.0000097002.69209.cd
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Alendronate Inhibits Systemic Innate Immunity and Reduces In-Stent Neointimal Hyperplasia in Rabbits

Abstract: Background-Innate immunity is of major importance in vascular repair. The present study evaluated whether systemic and transient depletion of monocytes and macrophages with liposome-encapsulated bisphosphonates inhibits experimental in-stent neointimal formation. Methods and Results-Rabbits fed on a hypercholesterolemic diet underwent bilateral iliac artery balloon denudation and stent deployment. Liposomal alendronate (3 or 6 mg/kg) was given concurrently with stenting. Monocyte counts were reduced by Ͼ90% 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 46 publications
3
80
0
1
Order By: Relevance
“…The degree of neointimal thickening was denoted as a unitless ratio of N/M area ( Table 2). N/M measurements were taken from the site of greatest luminal narrowing per artery, as this is the standard of the field and the most clinically relevant (19,30).…”
Section: Resultsmentioning
confidence: 99%
“…The degree of neointimal thickening was denoted as a unitless ratio of N/M area ( Table 2). N/M measurements were taken from the site of greatest luminal narrowing per artery, as this is the standard of the field and the most clinically relevant (19,30).…”
Section: Resultsmentioning
confidence: 99%
“…Macrophage content in atherectomy tissue and the activation status of blood monocytes correlate with an increased rate of restenosis in humans (57,58). Recently, we have shown that transient and partial depletion of circulating monocytes by particulate dosage forms such as polymeric NP and liposomes-laden BPs suppresses neointimal formation and reduces experimental restenosis (12)(13)(14)(15)(16). It is suggested that, similarly to liposomal BPs (14-16), the inhibition of stenosis was mediated via simvastatin liposomes accumulation in circulating monocytes and their inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that, similarly to liposomal BPs (14-16), the inhibition of stenosis was mediated via simvastatin liposomes accumulation in circulating monocytes and their inactivation. The partial and transient depletion of circulating monocytes results in reduced number of macrophages at the injury site and consequently with a diminished inflammatory response (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations